Results From an RCT on Brief Parent Training: Long Term Effects on Parental Quality of Life - Reedtz, Charlotte; Klest, Sihu K.; Aalo, Nora Mortensen; Rasmussen, Ingrid Daae; Vitterso, Joar (Frontiers in Psychology, 2019)
Background: Previous research has shown that quality of life for adults decreases when they become parents, remains at a lower level than of non-parents and declines further with each child they have. Consistent with this, parents report that having children leads to more daily struggles and concerns than their work outside the home. In this study, we have investigated how participating in a brief parent training intervention influences parents’ quality of life. The aim of the study was to evaluate whether a brief, six-session version of an evidence-based parent training programme (The Incredible Years), delivered in a non-clinical community sample, changed parent quality of life up to four years after the initial intervention. Methods: Data were collected from mothers and fathers in a randomized controlled community trial (N = 117). Children’s mean age was 3.95 years at baseline, and 7.5 years at 4-year follow-up. Results: There were no significant differences in the trajectory of change over the four time points between the intervention and control groups for mothers or fathers. However, results from analysing the linear change from pre to each of the other measurement points, revealed statistically significantly different change on life satisfaction after completing the intervention compared to the control group; immediately following the intervention, t(357) = 2.76, p = 0.006; and the difference between the groups was maintained three years after the intervention, t(360) = 3.14, p = 0.002. Conclusion: The results of this study suggest that offering a parenting program focused on building a positive parent-child relation, has the potential to improve mothers’ quality of life. Implications of this are discussed. Trial registration: ClinicalTrials.gov NCT02850510. Retrospectively registered 29 July 2016.